Lean manufacturing for SMEs: Enabling rapid response to demand changes - Achanga, Pius Coxwell; Shehab, Essam; Roy, Rajkumar; Nelder, Geoff (Cranfield University, 2005)
Small-to-medium-sized manufacturing enterprises (SMEs) make significant contributions to most national economies. In the UK for instance, SMEs account for up to 40% of gross domestic product (GDP) and 85% of newly created jobs. However, the current economic turnaround, fostered by recent technological advances in terms of e-commerce coupled with the advent of globalisation, has been felt in the manufacturing sector in general but more severely by SMEs. This paper aims to demonstrate through a case study approach how lean manufacturing can enable organisations to respond rapidly to sudden changes in customer demand.